Fidelização de clientes na web: como conhecer e fidelizar clientes por meio da internet - Benossi, Claudio (2010)
The paper entitled Loyalty of customers on the web: How to know the loyalty of customers through the internet. Technology Master of Intelligence and Digital Design (TIDD) aim to analyze the contribution technology of information to the relationship marketing increasing business competitiveness. The current global environment requires an age of competition result of disintegration of the border and the opening of previously protected markets. This scenery leads campanies to reorganize in two polo: the information technology and marketing. The information becomes the key factor to gain positioning and competitiveness advantage in the market. Relationship marketing is adopeted as a business philosophy focusing on understanding and attending the buyer behavior and consumer needs. The intensive use of information technology under their many forms (computers, telecommunications, network information, internet, software management, etc) helps to make efficient and profitable the company s relationship with its clients allowing them to collect, store, process, analyze, interpret and transmit the data relationship with them in its several sectors of the economy. Thus, establishing how the institutions can take advantage of the flow system and information over the customers, market environment obtained from the CRM Techology custumer Relationship Management to gain competitiveness. Starting from a brief review concept of CRM and analyzing electronic commerce will be described various categories such as E-business, E-Auctioning, E-banking, E-directories, E-Engineering, E-franchising, E-learning, E-marketing, E-Gambling, E-Procurement, E-recruiting to work out a comparative between electronic commerce and traditional commerce. Therefore, to approach we will discuss how the quality of service and the management of the customers satisfaction through the philosophy of CRM, combined with information technology may bring loyalty benefits of that customer anticipating the challenge of integration data, organizational and cultural changes of the new global economy